Boosting scientific publications in Africa: which IPRs protection channels matter? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This paper examines how Africa's share in the contribution to global scientific knowledge can be boosted with existing Intellectual Property Rights (IPRs) mechanisms. The findings which broadly indicate that tight IPRs are correlated with knowledge contribution can be summarized in two main points. First, the enshrinement of IPRs laws in a country's Constitution is a good condition for knowledge economy. Secondly, while Main IP laws, WIPO treaties and Bilateral treaties are positively correlated with scientific publications, the IPRs law channel have a negative correlation. Whereas the study remains expositional, it does however offer interesting insights into the need for IPRs in the promotion of knowledge contribution within sampled countries of the continent. Other policy implications are discussed.
Keywords: A20; F42; O34; O38; O55; 330; Publications; Intellectual property rights; Governance; Africa